Provision of veterinary services in livestock holdings in the Russian Federation - M. A. Shibayev; A. S. Oganesyan; A. Selyanin; A. V. Belchikhina; I. M/ Klinovitskaya; A. K. Karaulov (Ветеринария сегодня)
Being the primary link in the disease notiﬁcation system, specialists of the veterinary service in livestock holdings ensure continuous monitoring and control of animal health. This analysis includes assessment of the actual availability of veterinary services in the absolute majority of animal holdings in 85 Subjects of the Russian Federation. In total, the study covered 6,226,368 holdings for major livestock species, such as cattle and small ruminants, pigs, poultry, horses and fur animals. Small-scale holdings have been shown to account for the largest proportion (99.7%) of the total number of livestock farms, while the proportion of holdings where animal health control is daily organized has varied from 0.03% in fur farms to 3% in poultry farms. The signiﬁcant role of animal owners in small-scale holdings within the implementation of epizootological surveillance has been determined. It was revealed that the main populations of pigs, poultry and fur animals are concentrated in large-scale livestock farms. The study results indicate a relatively favorable situation in pig and poultry holdings, where only single cases of lack of veterinary service were reported. On the contrary there are multiple cases of lack of veterinary care in the farms for rearing cattle, small ruminants, fur animals. The paper highlights the mechanisms for the implementation of tasks assigned to the state veterinary service in terms of the organization of planned preventive and diagnostic veterinary measures in large pig breeding establishments. Proposals were made to introduce a legally ﬁxed obligation for animal owners in large-scale livestock holdings to establish and maintain the production veterinary service, as well as a proposal to establish divisions of the state veterinary service in large-scale livestock establishments.